SWOC Analysis for Competitiveness: Strategy Mapping of Wonoayu Shrimp Crackers: Analisis SWOT untuk Daya Saing: Peta Strategi Keripik Udang Wonoayu - Azis, Nadia Ismayanti; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The rapid growth of the business world necessitates that Micro, Small, and Medium Enterprises (MSMEs) adopt effective strategies to maintain competitiveness amidst intense global market rivalry. Specific Background MSMEs, like the Shrimp Cracker producers in Wonoayu, Sidoarjo, play a crucial role in the national economy but often face internal limitations and external challenges that require strategic management. Knowledge Gap Many MSMEs prioritize production over strategic planning, lacking a formal framework to link internal capacity with external market dynamics to gain advantage. Aims This study employs a qualitative method to analyze the obstacles facing Wonoayu Shrimp Cracker MSMEs using SWOC analysis and proposes solutions through risk management. Results The analysis places the UMKM in the Weakness-Opportunity (WO) strategic quadrant, indicating that existing external opportunities should be leveraged to minimize internal weaknesses. Novelty The research combines the SWOC framework with risk management principles to provide practical, zone-based risk mitigation strategies for local UMKM. Implications The findings suggest that by focusing on the WO strategy and actively managing identified risks, the UMKM can achieve better advantage and superior competitiveness. Highlights: Wonoayu Shrimp Cracker MSMEs are positioned in the Weakness-Opportunity (WO) strategic quadrant. SWOC analysis is applied in conjunction with risk management for strategy formulation. The strategic recommendation is to leverage external opportunities to counter internal business weaknesses. Keywords: SWOC Analysis, Risk Management, MSMEs, Shrimp Crackers, Weakness Opportunity